2022
DOI: 10.31234/osf.io/g42fb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of delay, length, and frequency on onset RTs and word durations: Articulatory planning uses flexible units but cannot be prepared

Abstract: Models of speech production differ about whether articulatory planning occurs online or offline and about whether a separate articulatory buffer is needed. The hypothesis that most articulatory planning is completed before articulation starts (offline) assumes a buffer where articulatory plans are accrued and kept ready before articulation starts. The hypothesis that articulatory planning can occur after the beginning of articulation (online) does not need a proper buffer but only limited memory resources en… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
1
0
0
Order By: Relevance
“…The fourth claim of Levinson and Torreira’s model is the distinction between response planning and launching: Speakers begin to prepare a response to their partner as soon as possible, but only launch it shortly before the anticipated end of the partner’s turn. This proposal is consistent with a large body of experimental work using delayed naming tasks, which has shown that speakers can indeed generate speech plans internally, retain them in working memory, and produce them upon presentation of a response cue (for recent discussions see Kawamoto, Liu, & Kello, 2015 ; Krause & Kawamoto, 2020 ; Piai, Roelofs, Rommers, Dahlstaett, & Maris, 2015 ; Romani, Silverstein, Ramoo, & Olson, 2022 ). The latencies to produce prepared utterances are much shorter than those observed for utterances not planned ahead of time.…”
Section: Utterances Are Planned Early and Launched Latersupporting
confidence: 83%
“…The fourth claim of Levinson and Torreira’s model is the distinction between response planning and launching: Speakers begin to prepare a response to their partner as soon as possible, but only launch it shortly before the anticipated end of the partner’s turn. This proposal is consistent with a large body of experimental work using delayed naming tasks, which has shown that speakers can indeed generate speech plans internally, retain them in working memory, and produce them upon presentation of a response cue (for recent discussions see Kawamoto, Liu, & Kello, 2015 ; Krause & Kawamoto, 2020 ; Piai, Roelofs, Rommers, Dahlstaett, & Maris, 2015 ; Romani, Silverstein, Ramoo, & Olson, 2022 ). The latencies to produce prepared utterances are much shorter than those observed for utterances not planned ahead of time.…”
Section: Utterances Are Planned Early and Launched Latersupporting
confidence: 83%